2016
DOI: 10.1371/journal.pone.0157499
|View full text |Cite|
|
Sign up to set email alerts
|

Burnout Subtypes and Absence of Self-Compassion in Primary Healthcare Professionals: A Cross-Sectional Study

Abstract: BackgroundPrimary healthcare professionals report high levels of distress and burnout. A new model of burnout has been developed to differentiate three clinical subtypes: ‘frenetic’, ‘underchallenged’ and ‘worn-out’. The aim of this study was to confirm the validity and reliability of the burnout subtype model in Spanish primary healthcare professionals, and to assess the explanatory power of the self-compassion construct as a possible protective factor.MethodThe study employed a cross-sectional design. A samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 73 publications
5
73
1
6
Order By: Relevance
“…Eleven empirical studies (Heffernan, Quinn Griffin, McNulty, & Fitzpatrick, ; Crarey, ; Senyuva, Kaya, Isik, & Bodur, ; Olson & Kemper, ; Olson, Kemper, & Mahan, ; Finlay‐Jones, Rees, & Kane, ; Kemper, Mo, & Khayat, ; Beaumont, Durkin, Hollis Martin, & Carson, ; Duarte, Pinto‐Gouveia, & Cruz, ; Durkin, Beaumont, Hollins Martin, & Carson, ; Montero‐Martin et al., ) reported on self‐compassion utilising a healthcare provider sample (Table ). Among these, eight studies investigated the role of self‐compassion on work‐related stress among healthcare providers (Crarey, ; Finlay‐Jones et al., ; Kemper et al., ; Olson et al., ; Beaumont et al., ; Duarte et al., ; Durkin et al., ; Montero‐Martin et al., ), and three studies reported on the positive impact of mindfulness and self‐compassion on healthcare provider resilience (Olson & Kemper, ; Olson et al., ; Kemper et al., ). Resilience, the process of coping with or overcoming exposure to adversity (Egeland, Carlson, & Sroufe, ), is considered a salient mitigator of burnout in healthcare providers (Weidlich & Ugarriza, ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven empirical studies (Heffernan, Quinn Griffin, McNulty, & Fitzpatrick, ; Crarey, ; Senyuva, Kaya, Isik, & Bodur, ; Olson & Kemper, ; Olson, Kemper, & Mahan, ; Finlay‐Jones, Rees, & Kane, ; Kemper, Mo, & Khayat, ; Beaumont, Durkin, Hollis Martin, & Carson, ; Duarte, Pinto‐Gouveia, & Cruz, ; Durkin, Beaumont, Hollins Martin, & Carson, ; Montero‐Martin et al., ) reported on self‐compassion utilising a healthcare provider sample (Table ). Among these, eight studies investigated the role of self‐compassion on work‐related stress among healthcare providers (Crarey, ; Finlay‐Jones et al., ; Kemper et al., ; Olson et al., ; Beaumont et al., ; Duarte et al., ; Durkin et al., ; Montero‐Martin et al., ), and three studies reported on the positive impact of mindfulness and self‐compassion on healthcare provider resilience (Olson & Kemper, ; Olson et al., ; Kemper et al., ). Resilience, the process of coping with or overcoming exposure to adversity (Egeland, Carlson, & Sroufe, ), is considered a salient mitigator of burnout in healthcare providers (Weidlich & Ugarriza, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research suggests that LKM is linked to increased mindfulness and self‐compassion (Galante, Galante, Bekkers, & Gallacher, ). In addition, mindfulness and self‐compassion scores appear to be negatively correlated to burnout (Barnard & Curry, ; Luken & Sammons, ; Montero‐Marin et al, , ). Given these findings, burnout resilience was operationalised as increased scores on mindfulness and self‐compassion outcomes.…”
Section: Present Studymentioning
confidence: 99%
“…Previous research has widely described the relationship between stress, burnout, the absence of self-compassion, and compassion fatigue (CF) among health professionals [7,8,9,10]. Studies from the United States and different countries in Europe report a prevalence of burnout from 27% up to 45% among practicing physicians, depending on the specialty, and especially note the prevalence of emotional exhaustion [3,4,11,12].…”
Section: Introductionmentioning
confidence: 99%